Role of the Ubiquitin Ligase RNF149 in the Development of Rat Neonatal Gonocytes - Manku, Gurpreet; Kong, Chi-Chon; Culty, Martine (Frontiers in Endocrinology, 2022)
Male reproductive function depends on the formation of spermatogonial stem cells from their neonatal precursors, the gonocytes. Previously, we identified several UPS enzymes dynamically altered during gonocyte differentiation. The present work focuses on understanding the role of the RING finger protein 149 (RNF149), an E3 ligase that we found to be strongly expressed in gonocytes and downregulated in spermatogonia. The quantification of RNF149 mRNA from postnatal day (PND) 2 to 35 (puberty) in rat testis, brain, liver, kidney, and heart indicated that its highest levels are found in the testis. RNF149 knock-down in PND3 rat gonocytes was performed to better understand its role in gonocyte development. While a proliferative cocktail of PDGF-BB and 17β-estradiol (P+E) increased both the expression levels of the cell proliferation marker PCNA and RNF149 in mock cells, the effects of P+E on both genes were reduced in cells treated with RNF149 siRNA, suggesting that RNF149 expression is regulated during gonocyte proliferation and that there might be a functional link between RNF149 and PCNA. To examine RNF149 subcellular localization, EGFP-tagged RNF149 vectors were constructed, after determining the rat testis RNF149 mRNA sequence. Surprisingly, two variant transcripts were expressed in rat tissues, predicting truncated proteins, one containing the PA and the other the RING functional domains. Transfection in mouse F9 embryonal carcinoma cells and C18-4 spermatogonial cell lines showed differential subcellular profiles of the two truncated proteins. Overall, the results of this study support a role for RNF149 in gonocyte proliferation and suggest its transcription to variant mRNAs resulting in two proteins with different functional domains. Future studies will examine the respective roles of these variant proteins in the cell lines and isolated gonocytes.